Reference jitter values for the sternocleidomastoid muscle with concentric needle electrodes - ULUÇ, KAYIHAN; KAHRAMAN KOYTAK, PINAR; TANRIDAĞ, TÜLİN (WILEY, 2021)
Background The aim of this study was to establish reference jitter values for the voluntary activated sternocleidomastoid (SCM) muscle using a concentric needle electrode (CNE). Methods The study included 39 healthy participants (20 female and 19 male) aged 18-77 y. Jitter was expressed as the mean consecutive difference (MCD) of 80-100 consecutive discharges. Filters were set at 1 and 10 kHz. The mean MCDs for all participants were pooled, and the mean value +2.5 SD was accepted as the upper limit for the mean MCD. The upper limit for individual MCD was calculated using +2.5 SD of the upper 10th percentile MCD for individual participants. Results Mean age of the participants was 45 +/- 14.5 y. Mean MCD was 16.20 +/- 2.23 mu s (range: 12-21 mu s), and the upper limit of normal for mean MCD was 21.8 mu s. The mean value for 823 individual jitters was 23.3 +/- 4.61 mu s (range: 6.6-36.9 mu s), and the upper limit of normal for each individual jitter was 34.6 mu s. Conclusions The present findings indicate that upper normal limit for mean MCD is 22 mu s and for individual data it is 35 mu s.
Keywords: concentric needle electrode; healthy participants; jitter; reference values; sternocleidomastoid muscle; SINGLE-FIBER EMG; ELECTROMYOGRAPHY